Faculty Perceptions of Expertise for Inclusive Education for Students With Significant Disabilities. (May 2021) - Kurth, Jennifer A.; Allcock, Heather; Walker, Virginia; Olson, Amy; Taub, Deborah
Teacher preparation for inclusive education of students with significant disabilities requires an understanding of the requisite skills and dispositions to be taught during the teacher preparation period. Given the relative scarcity of inclusive placements for this population, as well as limited research-based teacher preparation practices to promote inclusive education, a Delphi study was completed to query expert faculty on the priority skills and activities used in teacher preparation. Consensus emerged through the Delphi study over three rounds of surveys to faculty, centering on essential skills of special education teachers, practices used by faculty to teach and evaluate these skills, and conditions that support and constrain teacher development of these essential skills. Although faculty largely supported research-based practices, new areas emerged, including teacher leadership skills. Implications for research and practice are included.